Post-traumatic stress disorder, psychiatric comorbidities and associated factors among refugees in Nakivale camp in southwestern Uganda - Bapolisi, Achille Mwira; Song, Suzan J; Kesande, Claire; Rukundo, Godfrey Zari; Ashaba, Scholastic (Springer Nature, 2020)
Background: Armed conflict in Africa has led to displacement of over 24.2 million people, more than 1.4 million of whom are living in Uganda. Studies show that refugees living in Ugandan refugee settlements are at increased risk for post-traumatic stress disorder. However data on the prevalence of other mental health problems among refugees including depression, anxiety and substance use disorder among refugees in Uganda is lacking. Our aim was to determine the prevalence of post-traumatic stress disorder, its main psychiatric comorbidities and perceived psychosocial needs among refugees in Nakivale refugee camp. Methods: We conducted a cross-sectional survey of refugee camp residents (n = 387) from nine different countries of origin. Psychiatric disorders were assessed using the MINI International Neuropsychiatric Interview (MINI) and perceived needs by the Humanitarian Emerging Settings Perceived Needs Scale (HESPER). Results: The prevalence of psychiatric disorders was high among refugees as was the level of perceived needs. The most prevalent psychiatric disorders were generalized anxiety disorders (73%), post-traumatic stress disorder (PTSD) (67%), major depressive disorder (58%) and substance use disorders (30%). There was a higher level of comorbidity between PTSD and substance use disorder (OR = 5.13), major depressive disorder (OR = 4.04) and generalized anxiety disorder (OR = 3.27). In multivariate analysis, PTSD was positively associated with the perception of stress as a serious problem (OR = 6.52; P-value = 0.003), safety and protection for women in the community (OR = 2.35; P-value = 0.011), care for family (OR = 2.00; P-value = 0.035) and Place to live in (OR = 1.83; P-value = 0.04). After applying the Bonferroni correction, the perception of stress remained significantly associated with PTSD. Conclusion: Our findings suggest a strong association between PTSD, its main comorbidities and basic needs in Nakivale refugee camps. Mental health support should include psychological interventions as well as social assistance to improve the health of refugees
Keywords: PTSD; Depression; Anxiety; Alcohol abuse; Pyschosocial needs; Uganda; Refugees